An evaluation of synthetic indole derivatives as inhibitors of monoamine oxidase. Issue 9 (1st May 2016) - Chirkova, Zhanna V.; Kabanova, Mariya V.; Filimonov, Sergey I.; Abramov, Igor G.; Petzer, Anél; Petzer, Jacobus P.; Suponitsky, Kyrill Yu.
Graphical abstract: Indole derivatives and related compounds were evaluated as inhibitors of the human monoamine oxidases. Abstract: In a recent study we have shown that several indole-5, 6-dicarbonitrile derivatives are potent inhibitors of human monoamine oxidase (MAO) A and B. To expand on these results and to further determine structure–activity relationships (SARs) for MAO inhibition by this chemical class, the present study investigates the MAO inhibition properties of additional indole‐5, 6‐dicarbonitriles and related indole-5, 6-dicarboxylic acid and pyrrolo[3, 4‐ f ]indole‐5, 7‐dione derivatives. Among the active compounds two pyrrolo[3, 4‐ f ]indole‐5, 7‐dione derivatives inhibited MAO-A (4g ) and MAO-B (4d ) with IC50 values of 0.250 and 0.581 μM, respectively. In general indole-5, 6‐dicarbonitriles, however, exhibit higher MAO inhibition potencies while indole-5, 6-dicarboxylic acids are weak MAO inhibitors. Active MAO inhibitors such as4g and4d may be used as leads for the development of drugs for the treatment of disease states such as Parkinson's disease and depression. MAO inhibitors are also under investigation as potential agents for the treatment of prostate cancer, certain types of cardiomyopathies and Alzheimer's disease.